The effect of calving season on reproductive performance of Jersey cows - Ercan Soydan; Mehmet Kuran (Mljekarstvo)
Dairy records, containing 1269 lactation record of 462 Jersey dairy cows collected over 16 years, from an agricultural state farm were used. Data for reproductive performance of cows were also collected. Means of the herd for lactation milk yield, calving interval, days open, interval from calving to the first insemination, lactation length, gestation length and dry period were 3195.7±20.2 kg, 366.6±1.7 d, 92.9±1.6 d, 78.0±1.3 d, 301.7±1.1 d, 275.2±0.2 d and 69.3±0.8 d, respectively. The effect of calving season (winter, spring, summer and autumn) on reproductive performance for high, low and moderate milk-yield cows was investigated. Calving season affected the days from calving to first insemination in high and moderate yielding cows (P<0.001) while didn’t affect low yielding cows. In summer, days open in high yielding cows were 35 days longer compared to winter season (P<0.001) as observed for moderate yielding cows (P<0.01). In high yielding cows, calving interval was 18 days longer in spring compared to winter calving season. Calving season also affected the first service conception rate in high yielding cows (P<0.05). Services per conception in autumn were lower than the other seasons (P<0.001). In conclusion, high yielding dairy cows need more attention in summer season with respect to body condition score, dietary energy: protein ratio, uterus health and elimination of heat stress, to get more profit in dairy farm.